A regulação das formas de captação coletiva de recursos pela internet mediante emissão de valor mobiliário - Rodrigo Rocha Feres Ragil (2017)
The present study offers an analysis of the terms the uses of public fundraising through Internet would be subject to the regulation of the Comissão de Valores Mobiliários (CVM). It is investigated, under a regulatory bias, the reasons why the State found it necessary and desirable to engage in practices that represent, ultimately, a relevant tool for smaller companies to get access to credit and for people in general intended to invest their surplus funds in exchange of remuneration. It has been observed situations where ordinary people, with simple Internet access, are enabled to devote part of its financial resources to joint entrepreneurs who, in contrast to the investment, promise to formalize the investor entrance as a partner or a creditor. It is natural that the dynamic awakes the interest and the concern of the CVM, once investors start accessing a new channel to apply their own resources in projects managed by third parties without much control or oversight by the State. The appeal of dealing with popular savings is notorious, being expected that the activity attracts the attention of the regulatory agency. This concern was formally and progressively assumed by the CVM from 2016. In that year, the regulatory agency published the notice of public hearing SDM no. 06/2016, a reference document for the elaboration of the normative instruction no. 588/2017, which crystallized CVM formal position regarding public fundraising through Internet based on securities issuance. From then on, the subject became specifically regulated in the Brazilian legal system. For a better understanding of the terms by which the State intended to intervene on this matter, the study depicted the pre-regulatory scenario of public fundraising through Internet held until 2017. It was intended to scientifically demonstrate that the agreements between companies and investors through funding portals could be qualified or admitted as underlying cause of securities issuance pursuant to art. 2 of law no 6.385/1976. This seemed to be the subsumption exercise used by the legislator to decide to formally intervene on the sector. The analytical description of this scenario was based on the understanding of how available platforms for investment in Brazil work and operate. It represented a fundamental stage for the qualification of the legal transactions that were used before IN CVM n. 588/2017 issuance for the practice of public fundraising through Internet. The subsumption exercise between the legal transactions and the CVM regulation required an analysis over the agency competence regime. The understanding of this "regulatory path" enriched the analysis over the activity ("Investment Crowdfunding) regulated by IN CVM 588/2017, whose main provisions were subject of a descriptive and an analytical synthesis. The study aimed to inaugurate some reflections on an activity and a sector recently regulated by the Brazilian State. In order to complement this analysis, it was finally presented a piece of compared law, grounded on the differences between the regulation in the United States of America and in Taiwan. The disparity in the way the State understands and intervenes on the practice of public fundraising in each of these systems contributed to a perspective analysis of the proposed regulation in Brazil.